Facilitating Word Retrieval in Aphasia: Which Type of Cues for Which Aphasic Speakers? - Python, Grégoire; Pellet Cheneval, Pauline; Bonnans, Caroline; Laganaro, Marina (Frontiers in Human Neuroscience, 2021)
Background: Even if both phonological and semantic cues can facilitate word retrieval in aphasia, it remains unclear if their respective effectiveness varies according to the underlying anomic profile. Aim: The aim of the present facilitation study is to compare the effect of phonological and semantic cues on picture naming accuracy and speed in different types of anomia. Methods: In the present within-subject design study, fifteen aphasic persons following brain damage underwent picture naming paradigms with semantic cues (categorically- or associatively-related) and phonological cues (initial phoneme presented auditorily, visually or both). Results: At the group level, semantic cueing was as effective as phonological cueing to significantly speed up picture naming. However, while phonological cues were effective regardless of the anomic profile, semantic cueing effects varied depending on the type of anomia. Participants with mixed anomia showed facilitation after both semantic categorical and associative cues, but individuals with lexical-phonological anomia only after categorical cues. Crucially, semantic cues were ineffective for participants with lexical-semantic anomia. These disparities were confirmed by categorical semantic facilitation decreasing when semantic/omission errors prevailed in the anomic profile, but increasing alongside phonological errors. Conclusions: The effectiveness of phonological vs semantic cues seems related to the underlying anomic profile: phonological cues benefit any type of anomia, but semantic cues only lexical-phonological or mixed anomia.